Measurement of the Calf Muscle Circumference is Useful for Diagnosing Sarcopenia in Older Adults Requiring Long-Term Care - Ryo Sato; Yohei Sawaya; Tamaki Hirose; Takahiro Shiba; Lu Yin; Shuntaro Tsuji; Masahiro Ishizaka; Tomohiko Urano (Annals of Geriatric Medicine and Research)
Background Calf muscle circumference is a potential alternative for measuring skeletal muscle mass. However, the association between calf muscle circumference and sarcopenia and the reliability of sarcopenia diagnosis based on calf muscle circumference have not been well reported. In this study, we aimed to determine the usefulness of calf muscle circumference measurement in the diagnosis of sarcopenia. Methods A cross-sectional study was conducted using data collected from 63 older adults (40 male and 23 female; mean age, 79.7±6.5 years) using day-care rehabilitation. Sarcopenia was defined according to the guidelines of the 2019 Asian Working Group for Sarcopenia (AWGS 2019). The association between sarcopenia and calf muscle circumference was determined using multiple regression analysis, and the reliability of sarcopenia diagnosis based on calf muscle circumference was determined using the kappa coefficient. Results Overall, 36.5% (30.4% female and 40.0% male) of the participants had sarcopenia. Calf muscle circumference was independently associated with sarcopenia. The best cutoff points for calf muscle circumference to identify older adults at risk of low skeletal muscle mass were 28.7 cm and 31.1 cm for female and male participants, respectively. Furthermore, the kappa coefficient between sarcopenia diagnosed using calf muscle circumference and that diagnosed using the AWGS 2019 criteria was 0.80. Conclusions Calf muscle circumference is independently and significantly associated with sarcopenia in older adults requiring long-term care. Calf muscle circumference is a surrogate for skeletal muscle mass and thus may be used to diagnose sarcopenia.